Penegakan Hukum Terhadap Pengemis Di Muka Umum Berdasarkan Pasal 504 Kitab Undang-Undang Hukum Pidana Oleh Kepolisian Resor Kota Pekanbaru - Rut Lamria Kristina Tambunan; Erdianto Effendi; Junaidi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Activity of begging in public is one of social illness need to be prevented and tackled because impact of implementation is a disruption of public order. As a state apparatus implement function of law enforcement, maintenance of security and public order and to protect, shelter and community service, The Police on duty to prevent and tackle the crime of begging. The problems in this thesis are how is arrangement of the crime of begging in positive law in Indonesia, how to applying of implementation on The Police tackle crime of begging and what are obstacles of The Police tackle the crime of begging. In the positive law in Indonesia, both regulated by article 504 Criminal Code and regulated as set out in Government Regulation 1980 Number 31 about Combatting Homeless and Beggars, all of define beggars as public order offense that in the practice need to be prevented and tackled.The purposes of writing this essay are; first The implementation of the enforcement of the law against beggars in public based on Article 504 Criminal Code by The Police Resort Town of Pekanbaru, second, any obstacles faced by The Police Resort Town of Pekanbaru. The type of research is classified on sociological legal research is looked at effectiveness of law in force by looking correlation between law with society, so it can reveal effectiveness of the rule of law in the society.Result of studies of this essay are: first, the enforcement of the law against beggars in public based the Article 504 Criminal Code still not has been effectively, evidenced by the number of beggars is found at the intersection of Arengka Market, Mall of SKA, Arifin Ahmad street and under the flyover at Sudirman street but none given criminal sanctions while begging in public area is included in a criminal offense. Second, obstacles faced in enforcing the law against begging in public are lack of knowledge by The Police Resort Town of Pekanbaru about The Article 504 Criminal Code and to assume a more dominant beggars is handled by Department of Social of Pekanbaru and Civil Service Police of Pekanbaru.Keywords: Enforcement of Law, Begging in public.